1987
DOI: 10.1089/jir.1987.7.657
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the Murine Mx Protein into the Nucleus Is Dependent on a Basic Carboxy-Terminal Sequence

Abstract: Cytoplasmic microinjection of murine Mx mRNA synthesized in vitro or nuclear microinjection of Mx cDNA under the control of a constitutive promoter into murine Mx- cells led to the accumulation of Mx protein in the nucleus and inhibited the replication of influenza virus but not of vesicular stomatitis virus (VSV). Similar results were also found with dog, rat, chicken, and monkey cells. A human lung fibroblast cell line (A549) was exceptional in that Mx protein was located predominantly in the cytoplasm and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…1A). The C terminus of rodent Mx1 protein is unique in that it contains a functional nuclear localization signal (NLS) (amino acids 606 to 615) (70,71). Mouse Mx1 accumulates in the nuclei of most cell types tested, and this localization is important for its antiviral activity (70,72).…”
Section: Middle Domain and Gtpase Effector Domainmentioning
confidence: 99%
“…1A). The C terminus of rodent Mx1 protein is unique in that it contains a functional nuclear localization signal (NLS) (amino acids 606 to 615) (70,71). Mouse Mx1 accumulates in the nuclei of most cell types tested, and this localization is important for its antiviral activity (70,72).…”
Section: Middle Domain and Gtpase Effector Domainmentioning
confidence: 99%
“…Biochemical analysis indicated that Mxl is a GTP-binding protein with GTPase activity (Nakayama et al, 1991(Nakayama et al, , 1992Mel6n et al, 1994) and that Mxl forms self-assemblies (Nakayama et al, 1993). The functional domains of Mxl involved in GTPbinding, GTP hydrolysis, self-assembly, di-and trimerization, and nuclear localization have been mapped (Noteborn et al, 1987;Nakayama et al, 1991Nakayama et al, , 1992Nakayama et al, , 1993MelOn et al, 1992MelOn et al, , 1994. Mutant analysis indicated that nuclear localization, GTP binding and GTPase activities, and dimer or trimer formation are essential for its anti-influenza virus activity (Ztircher et al, 1992;Garber et al, 1993;Pitossi et al, 1993 The fragments containing Mxl and its mutant cDNA, S50I, were cloned from pTrpA12Mx and pS50I (Nakayama et al, 1991), respectively, into the expression vector pCB6 (obtained from Dr M. Roth, University of Texas, Tex., USA, with permission from Dr M. Stinski, University of Iowa, Iowa, USA) between BglII and HindIII to create pCBMxl and pCBS50I, respectively.…”
Section: Role Of Gtpase Activity Of Murine MXL Protein In Nuclear Locmentioning
confidence: 99%
“…1). It is known that human MxA and mouse Mx2 are localized in the cytoplasm (Leong et al 1998), and that nuclear retention requires a nuclear localization signal (NLS) motif, characterized by a short stretch of positively charged residues (K/L) near the carboxylic acid terminus of a protein (Noteborn et al 1987). Crucian carp Mx proteins bear a slightly greater identity both to MxA and to Mx2, compared with their counterparts MxB in human and Mx1 in mouse, respectively (Table 2), and they both do not contain a NLS (Fig.…”
mentioning
confidence: 99%